Spatial dynamics of costs on technological innovations as an internal factor of innovative economy construction in Russia - D. A. Ruban (Новые технологии, 2017)
Allocation of costs for technological innovations across Russian regions has changed little during 2010-2014-s, that is in many respects favorable for the formation of an appropriate investment attractiveness of the country and regions. This factor should be taken into account in state programs and strategies for building an innovative economy.